MODEL PEMBELAJARAN HYBRID LEARNING TERHADAP KEMANDIRIAN BELAJAR PEMBUATAN ASKEB KB MAHASISWI KEBIDANAN - nursyahraeni madika rahman nunu; Sutina Made; Nilawati Usman (Jurnal Suara Kesehatan, 2023)
As a result of government regulations regarding the learning process using the hybrid learning method, which originally only used online learning methods in tertiary institutions. The purpose of this study was to find out the implementation of the hybrid learning model for midwifery student learning independence at AKBID Tahirah Al Baeti Bulukumba. This study uses a descriptive quantitative approach by using percentages for data analysis, the sampling technique is purposive sampling with a total of 45 respondents. The data collection used was a questionnaire in the form of questions using a Likert scale. The research results of the hybrid learning model are classified as very good, as evidenced by the results of the questionnaire distributed to 45 respondents at intervals of 75% - 100%, namely 85%.